'Vacant Geelong' and its lingering industrial architecture. Issue 4 (2nd December 2020) - Lozanovska, Mirjana; Nakai Kidd, Akari
Abstract : Once a prosperous manufacturing town, Geelong in Victoria, Australia is undergoing a process of deindustrialisation and, in turn, redefining its identity to better retain viability in a globalised world. For instance, the town bid to host a Guggenheim museum on its Eastern Beach shore at the turn of the millennium, and has recently become a UNESCO City of Design (2017). Like so many declining regional industrial towns, Geelong has been undercut by the new economic forces, and has sought a new identity in cultural economies. The 'Vacant Geelong' project, which began at Deakin University in 2015 and is ongoing, evolved as a response to vacant industrial architecture in Geelong. Major industries including Ford (vehicles), Alcoa (aluminium), timber sawmills, wool mills, Pilkington Glass, cement works, and the oil refinery once defined the town and its history as an industrial architectural landscape. 1 Major industries transformed the architectural and cultural terrain. Despite these cycles of transformation and erasure, and counter to a progressive and chronological approach to change, the 'Vacant Geelong' project explored this vacancy of industrial operation, yet presence of industrial architecture. Through inscriptions – artworks, design projects, creative research, installations, texts – it addressed those material realities that did not leave, the industrial structures – silos, ducts, chimneys, warehouses – that give Geelong its continuing industrial architectural character.